Political Communication Ethics in Pressure Groups: WALHI’s Campaign to Defend Rempang - Khoir Ilmuan; Vani Musyfiqoh; Aufah Syarfilah; Devi Mariska; Muh. Yahya Saraka; Shulhan Rumaru (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
This study analyzes the application of political communication ethics by WALHI Nasional as part of Indonesia’s political infrastructure, particularly in the Bela Rempang movement. This movement represents community resistance against perceived government hegemony during the development of the Rempang Eco City National Strategic Project. The project is seen as neglecting the community’s needs and desires, leading to conflicts due to communication errors. The study aims to understand the strategies and ethical practices employed by WALHI Nasional in navigating this sensitive and conflict-prone issue. Using a descriptive case study method and a critical paradigm, the research reveals that WALHI Nasional employs five core strategies in its advocacy: assessing, protecting, promoting, educating, and supporting the community. These strategies align with the principles of political communication ethics proposed by Karl R. Wallace and Sidney Hook. The findings suggest that WALHI Nasional adheres to ethical communication practices, emphasizing transparency and community empowerment. In contrast, the political superstructure, represented by the government, appears to neglect ethical considerations in its approach, exacerbating tensions and conflicts. This disparity highlights the importance of ethical communication in addressing sensitive issues and fostering mutual understanding between stakeholders.